Efficacy of diet restriction with or without probiotic for treatment of patients with IBS‐D: Phase I−II clinical trial - Xian‐Shu Zhao; Li‐Jun Shi; Bao‐Li Ning; Zhi‐Ming Zhao; Xiao‐Xue Li; Meng‐Hua Zhu; Ya‐Bing Zhang; Jun Fu (Immunity, Inflammation and Disease)
Abstract Background and Aim Diet is a major contributor to irritable bowel syndrome (IBS) and is also a powerful tool for treatment of IBS. This study compared two diets and explored the effectiveness of the diets when combined with a probiotic for treatment of IBS‐D patients. Methods Phase I, patients were randomized into groups; control, cold/spicy/fried restricted diet (CSF res diet), IgG positive restricted diet (IgG res diet), and a combination both diets (CSF + IgG res diet). Phase II, patients were randomized into IgG res diet + placebo and IgG res diet + probiotic. Both interventions were 12 weeks in duration. Symptom Severity Scale (IBS‐D‐SSS) and IgG titer were assessed at the beginning and the end of the study. Results Totals of 214 and 167 patients completed the two parts of the study, respectively. After intervention, IBS‐D‐SSS and TIgG grade were significantly improved compared to baseline, with results similar to the control group. In general, there were decreases in IBS‐D‐SSS and TIgG grade that were significantly different among the groups. There were exceptions; no differences were observed for IBS‐D‐SSS between the IgG res diet and CSF + IgG res diet, or TIgG grade between the CSF res diet, IgG res diet, and CSF + IgG res diet. However, the CSF res diet and IgG res diet had a synergistic effect that decreased IBS‐D‐SSS and TIgG titer, with a greater contribution by the IgG res diet. Therefore, we evaluated the IgG res diet with either placebo or probiotic and found that IBS‐D‐SSS and TIgG grade decreased from baseline. There was a significant decrease in IBS‐D‐SSS with the probiotic but TIgG grade was not significantly different between the IgG diet + placebo and IgG diet + probiotic diet. Conclusions Both the CSF res diet and IgG res diet improved IBS symptoms and demonstrated synergy, although the IgG res diet had a greater contribution. Further, when intolerant foods cannot be eliminated from a diet, avoiding uncooked, cold, spicy, fried, and alcoholic foods is a superior choice. The IgG res diet combined with Bifidobacteria was the best dietary choice and may function though a non‐IgG pathway.